Pinpointing Poverty in Europe : New Evidence for Policy Making - Simler, Kenneth (World Bank, Washington, DC, 2016)
Because the World Bank and the EU have the common objective of building competitive and sustainable economies and reducing poverty and social exclusion and because of the World Bank’s extensive experience, the EC and the Bank entered into an agreement to assist EU member states in undertaking expert analysis of census and survey data to create accurate, detailed geographical presentations of poverty. This note highlights the context and main findings of the ongoing European Commission (EC)–World Bank project, Poverty Mapping in the European Union, including the EU goals of reducing poverty and social exclusion and the difficulties of precisely identifying the poor in the EU.